Local Wisdom-Based Learning Planning Development of Borobudur Tourist Village to Improve Early Childhood Creativity - Wartani, Eka; Yuliantina, Irma (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Educators/teachers must be able to create learning activities that are not only fun and interactive, but also in accordance with children's needs. Quality learning arises from the teacher's ability to activate children's participation through appropriate learning planning. One effective strategy is to include elements of local wisdom in the plan. Although the curriculum provides great opportunities for teachers to design innovative learning, the reality in the field shows that many educators still have difficulty integrating local wisdom effectively. Many of them do not yet have guidelines such as teaching modules or Learning Implementation Plans that link to local wisdom. Therefore, this study aims to develop learning planning based on local wisdom and assess the feasibility of the development product to increase the creativity of early childhood. This study uses the research and development methodology (Research and Development Methodology) using the 4-D model design (Four D Models). This includes 4 stages, namely the definition stage (define), design (design), development (develop) and dissemination (disseminate). However, this study is limited to the development stage.The subjects of the study were PAUD Educators in Borobudur District. Data were collected through interviews to analyze needs and using questionnaires by three expert validations (material, local wisdom and PAUD practitioners). The material expert validator gave a total score of 66 in the very good category interval, the local wisdom expert validator gave a score of 51 in the good category interval. The PAUD practitioner validator gave a score of 74 in the very good category interval. From the results obtained above, it can be concluded that this lesson planning product is suitable for use after being revised based on suggestions for improvement from experts.